'Inner' suburbanisation – Background of the phenomenon in a polycentric, post-socialist and post-industrial region. Example from the Katowice conurbation, Poland. (September 2020) - Spórna, Tomasz; Krzysztofik, Robert
Abstract: The article discusses the issue of 'inner' suburbanisation – a unique spatial and social phenomenon. The process of 'inner' suburbanisation involves the development of low-rise housing estates (characteristic of 'classical' suburban architecture) within highly urbanised areas. This phenomenon, with its anti-sprawl effect, develops in polycentric systems on account of the specific distribution of ground rent and the availability of free land for new housing developments. This paper presents 'inner' suburbanisation in a post-industrial example, in the post-socialist Katowice conurbation in southern Poland. Referring to that example, the factors of the advancement of 'inner' suburbanisation are discussed, as well as the typology of spatial manifestations of this process within the metropolitan core. It was established that 'inner' suburbanisation processes developed in the surroundings of most towns in the core of the polycentric urban region. Graphical abstract: Unlabelled Image Highlights: Different types of suburbanisation have been identified in the post-socialist, post-industrial polycentric urban region (PUR) Urban development in the Katowice conurbation is directed at suburbanisation occurring both in the core and outer zone Self-reinforcing factors and the economic transition caused the growth of 'inner' suburbanisation in the Katowice conurbation The suburbanisation process can develop not only outside cities but also within their administrative limits The phenomenon of 'inner' suburbanisation can explain the spatial development of some post-socialist and polycentric urban regions